Cavernoma‐related epilepsy: Review and recommendations for management—Report of the Surgical Task Force of the ILAE Commission on Therapeutic Strategies. Issue 12 (17th October 2013) - Rosenow, Felix; Alonso‐Vanegas, Mario A.; Baumgartner, Christoph; Blümcke, Ingmar; Carreño, Maria; Gizewski, Elke R.; Hamer, Hajo M.; Knake, Susanne; Kahane, Philippe; Lüders, Hans O.; Mathern, Gary W.; Menzler, Katja; et al.
Summary Cerebral cavernous malformations (CCMs) are well‐defined, mostly singular lesions present in 0.4–0.9% of the population. Epileptic seizures are the most frequent symptom in patients with CCMs and have a great impact on social function and quality of life. However, patients with CCM‐related epilepsy (CRE) who undergo surgical resection achieve postoperative seizure freedom in only about 75% of cases. This is frequently because insufficient efforts are made to adequately define and resect the epileptogenic zone. The Surgical Task Force of the Commission on Therapeutics of the International League Against Epilepsy (ILAE) and invited experts reviewed the pertinent literature on CRE. Definitions of definitive and probable CRE are suggested, and recommendations regarding the diagnostic evaluation and etiology‐specific management of patients with CRE are made. Prospective trials are needed to determine when and how surgery should be done and to define the relations of the hemosiderin rim to the epileptogenic zone.